ATMOSPHERE PROTECTION FROM POLLUTION DUE TO SPILLS OF TOXIC SUBSTANCES - Biliaiev, M. M.; Koptilaia, O. V. (Science and Transport Progress, 2005)
A method to calculate the process of contaminated air evacuation from the zone of toxic substance spillage with ventilators has been developed. The method is based on the numerical integration of 3D equation of pollutant transfer. Results of the calculative experiment have been provided.